NILAI KELESTARIAN ALAM DAN HUBUNGAN SPIRITUAL DALAM CERPEN “AMA TEWO” KARYA SILVESTER PETARA HURIT - Sirilus Karolus Keroponama Keban; Yohana Hingi Tefa (LPPM Universitas Bina Bangsa, 2025)
This study aims to describe the values of nature conservation and spiritual relationships in the short story